(untitled) (Cultura Económica, 2021)
This paper compares the place occupied by the question of the possibility and viability of capitalist civilization in the philosophical projects of Adam Smith and Henri Bergson. It is reconstructed how, and to what extent, these two authors conceive the transition between particular human societies and a worldwide human society of world mediated by the commercial relationship; what hopes and dangers do they consider to be looming in that process, and if they examine (or not) necessary and pertinent to integrate into their respective philosophical projects the question about the historical conditions and circumstances that can make the realization of the promises of modernity possible.